THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT STATE MIDDLE SCHOOL 1 TELUKDALAN SOUTH NIAS - Maduwu, Fridawati; T. M. Sirait, Ronnie; Simanjuntak, Markus Doddy (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of leadership and work motivation on the performance of employees of SMP Negeri 1 Telukdalam, South Nias. The influence of leadership and work motivation is analyzed partially and simultaneously on the performance of employees of SMP Negeri I Telukdalam, South Nias. The research method used is quantitative descriptive research. The data collection technique uses a questionnaire distributed directly to teachers and non-teaching staff at SMPN I Telukdalam using a questionnaire. The sample in this study was 96 teachers and non-teaching staff at SMPN I Telukdalam. The analysis methods used are validity test, reliability test, heteroscedasticity test, classical assumption test, multiple linear regression analysis and hypothesis test. The results of the study indicate that the variables of leadership quality (X1) and work motivation (X2) are significant on employee performance (Y). Therefore, it can be concluded that the influence of each variable partially influences and simultaneously also influences the performance of employees of SMPN I Telukdalam. Data is processed statistically using the SPSS 26 program tool